Strategic Interaction in Auditing: An Analysis of Auditors' Legal Liability, Internal Control System Quality, and Audit Effort - Pae, Suil; Yoo, Seung-Weon (The Accounting Review, 2001)
This paper presents a model in which a firm's owner, an auditor, and outside investors strategically interact. The owner's investment in the quality of the firm's internal control system and the auditor's effort jointly affect the informativeness of the auditor's report on the firm's financial statements. If the auditor's legal liability to investors is large, then an efficiency loss arises because the owner underinvests in the internal control system and the auditor overinvests effort. On the other hand, if the liability is small, then an efficiency loss arises from the owner's overinvestment and the auditor's underinvestment. Regulators can improve allocative efficiency by changing the auditor's legal liability. However, in our model, it is impossible to completely eliminate the efficiency loss by changing the auditor's liability alone, because no damage award can induce both the owner and auditor to make socially optimal investments in the internal control system and audit effort. We also interpret recent changes in the regulatory environment in the context of our model.